Otomatisasi Penjadwalan Pemberian Pakan Ikan Menggunakan Fuzzy Logic Rules Based System - Hantoro, Kusdarnowo (Journal of Informatic and Information Security, 2024)
This study aims to design and build an efficient and effective automatic feeding device for comet fish. This tool is designed to overcome the problem of inaccuracy in the time and amount of manual feeding, as well as maintaining the quality of pond water. The method used is to combine a microcontroller system, water level sensor, and servo motor to regulate the dose and time of feeding. The results of the study show that this tool is able to provide food automatically according to the program, so that it can increase fish growth and maintain pond cleanliness. In providing scheduled comet fish feed, the method used in this study is the Rule Based System which is used as an automatic comet fish feeding schedule.